2018
DOI: 10.1002/chem.201801588
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bismuth‐Based Nanomaterials Used for Cancer Diagnosis and Therapy

Abstract: Theranostic nanomaterials (NMs) have gained increasing attention for their simultaneous performance of diagnosis and therapy. Bi-based NMs hold great potential as theranostic platforms based on their X-ray sensitive capability, near-infrared driven semiconductor properties, and distinctive structures, which facilitate the computed tomography (CT) imaging, photoacoustic (PA) imaging, radiation therapy, and phototherapy. The sophisticated design in composition, structure, and surface fabrication of Bi-based NMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 152 publications
0
38
0
Order By: Relevance
“…Among the many different biological advantages of bismuth, the most effective and commonly studied is its use in the treatment of gastrointestinal disorders [43]. The earliest recorded use of bismuth is for the protection and healing of skin and ulcers [44].…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Among the many different biological advantages of bismuth, the most effective and commonly studied is its use in the treatment of gastrointestinal disorders [43]. The earliest recorded use of bismuth is for the protection and healing of skin and ulcers [44].…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…These properties of Bi have made it an important nanomaterial in different fields such as diagnosis and therapy of cancer. Some studies have shown that Bismuthbased nanomaterials such as its oxides, sulfides, and selenide are outstanding materials for radiotherapy enhancement performances and computed tomography contrast [85]. Coreshell heterojunctions can be used for building theranostic by combining these materials with other magnetic resonance enhancement nanomaterials (MnSe, MnS, and Fe 3 O 4 ).…”
Section: Bismuth-peg Based Nanocarrier For Combination Therapy In Lung Cancermentioning
confidence: 99%
“…This targeted chemotherapeutic agent uses apoptosis and narcosis to kill cancerous cells. 21–23 An emerging generation of nanocarrier is 2D nanomaterials, such as tungsten diselenide 24 (WSe 2 ), silicene, 25 germanene, 26 molybdenum disulfide 27 (MoS 2 ), bismuth selenide 28 (Bi 2 Se 3 ), manganese dioxide, 29 transition metal di-chalcogenides (TMDs), hexagonal boron nitride 30 (h-BN), and GRP are some important nanocarriers due to their specified and unique physicochemical properties. 31–34 GRP created a honeycomb 2D crystal lattice structure in which all carbon atoms are sp 2 hybridized, leading to incredible mechanical and electrical performance is commonly used in optoelectronic devices, in a solar cell as photoconductive material, in drug delivery, and medical imaging due to the presence of good surface reactivity and free π electrons.…”
Section: Introductionmentioning
confidence: 99%